Dosimetry evaluation based on radiation interaction probability of Rhizophora spp. bonded with soy protein phantom for medical physics applications - Rabaiee, Nor Ain; Abdul Aziz, Mohd Zahri; Tajuddin, Abdul Aziz; Hashim, Rokiah (Faculty of Medicine Universiti Kebangsaan Malaysia, 2023)
Introduction: Tissue equivalent phantom (TEP) materials are effective tools for medical physics development, optimisation, and performance evaluation. A Malaysian mangrove wood, Rhizophora spp. (R.spp) bonded with soy protein phantom, was studied as a potential TEP in medical physics application. The aim of this study is to determine the radiation probability interaction of R. spp bonded with soy protein phantom. Materials and Methods: The R.spp bonded with soy protein was evaluated for its elemental composition. Then, the probability of photon interaction was obtained at energy from 1 keV to 50 MeV using a Monte Carlo simulation with EGSnrc PEGS4 (EGSnrc – electron gamma shower by National Research Council, PEGS4 – pre-electron gamma shower 4). The EGSnrc PEGS4 was used to interpolate experimental results and compared with that of water and solid water phantoms. Results: The identical curve was observed at three different media; R.spp bonded with soy protein phantom, solid water phantom and water phantom for different photon interaction; photoelectric absorption, Compton scattering and pair production between the energy range of 1 keV to 50 MeV. Conclusion: The R.spp bonded with soy protein particleboard phantom was shown to be ideal for use in medical physics dosimetry as TEP material.